Semi-empirical method of studying the D-layer aeronomy. II. Evidence-based calibration of the method - Kozlov, Stanislav; Nikolaishvily, Sergey (Solar-terrestrial physics, 2024)
This paper presents the results of evidence-based calibration of a new semi-empirical method for studying the D-layer aeronomy. We use simultaneous measurements of altitude profiles of electron density Ne(h) and ionization rate q(h) under disturbed conditions (case 1) and mean under various heliogeophysical conditions at low (LSA) and high (HSA) solar activity (case 2). The experimental data and methods are described in detail. It is shown that it is necessary to include temperature dependences of rate constants T(h) for all heliogeophysical conditions. Care should be taken when choosing the T(h) distribution with due regard to most of known factors having an effect on it, wherever possible. We draw a conclusion on the practicability of the use of new photodetachment rates that depend on the solar zenith angle and h. The unknown dissociative recombination rate for cluster positive ions and the photodetachment rate can be reasonably considered as free parameters, of course within due limits. Under disturbed ionospheric conditions, the evidence shows a fall in Ne at all altitudes h when q≈(1.3÷2)⋅10² cm⁻³ s⁻¹ with further increase in the parameters with q, which is confirmed by calculations using the semi-empirical model, yet for a wider range of q variations. The theoretical model that explains the aforementioned effect is the subject of future study. The results for dayside coincide qualitatively with our knowledge on the behavior of aeronomy parameters in the D layer. The studies suggest that the presented method allows qualitative estimations under all heliogeophysical conditions and even wholly satisfactory quantitative estimations under disturbed ionospheric conditions.